SCHOOL-BASED INTERVENTIONS FOR PROMOTING PSYCHOLOGICAL RESILIENCE AND WELL-BEING IN CHILDREN - Natalya Pavlova; Igor Vasiliev; Noorhani Dyani Laksmi (Yayasan Adra Karima Hubbi, 2026)
Psychological resilience and emotional well-being are fundamental determinants of children’s healthy development, academic engagement, and long-term mental health. Increasing exposure to academic pressure, social challenges, family instability, and environmental stressors has intensified the need for preventive school-based interventions that strengthen children’s adaptive capacities before psychological difficulties become more severe. This study aimed to examine the effectiveness of comprehensive school-based interventions in promoting psychological resilience and well-being among primary school children. A mixed-methods sequential explanatory design was employed involving 960 students from ten elementary schools implementing resilience-oriented educational programs. Quantitative data were collected using validated measures of psychological resilience, emotional well-being, emotional regulation, self-efficacy, school connectedness, and social competence, and analyzed through generalized linear mixed-effects modeling, structural equation modeling, mediation analysis, and repeated-measures analysis of variance. Qualitative evidence was obtained through interviews, focus group discussions, classroom observations, and institutional document analysis, followed by thematic interpretation. Findings revealed significant improvements in psychological resilience, emotional well-being, adaptive coping, emotional regulation, self-efficacy, school connectedness, and academic engagement, supported by stronger teacher support, positive peer relationships, and greater family involvement. Psychological resilience emerged as the principal mechanism linking school-based interventions with improved well-being and positive educational outcomes. Results indicate that sustainable child well-being depends on coordinated interaction among resilience education, supportive school climate, teacher engagement, counseling services, and family participation. The proposed framework offers practical guidance for developing comprehensive whole-school programs that foster children’s psychological resilience and lifelong well-being